Biological Kinetic Model Design and Development for Low-Loading River Water Treatment Plant (RWTP) - Mohiyaden H.A.; Sidek L.M.; Salih G.H.A. (Springer Science and Business Media Deutschland GmbH, 2024)
Recent research has identified that the major fraction of kinetic model in any type of wastewater. The research presented herein develops the kinetics of low-loading wastewater removal and river water treatment plant as a launch pad. Kinetic laboratory was developed with the setup of 2-h hydraulic retention time (HRT) in integrated Fixed Activated Sludge System (IFAS) bioreactor operation toward biological performance. Two bioreactors were installed with two different types of biological carrier which was applied in full-scale RWTP and was fed with synthetic river water. The setting-up including concentration of the carrier was followed the manufacturers design same as full-scale RWTP. The testing happened for 28days non-stop. In biological kinetic parameter estimation, according to the Monod model, it can be observed that values obtained for biokinetic coefficients for brush media and Bioball are k as 4.65days?1 and 1.37days?1 while ?max as 5.11days?1 and 1.424days?1 respectively. The model validation test and bio-kinetic parameters of brush media models have shown better simulation results compared to Bioball bio-kinetic parameters. This was proven with root mean square error (RMSE) value (8.26) for brush media, which is lesser than 47.1369 RMSE value (29.08). These findings provide evidence of the best performance and operation of RWTPs